Genetic Diversity and Conservation Units: Dealing With the Species-Population Continuum in the Age of Genomics - Coates, David J.; Byrne, Margaret; Moritz, Craig (Frontiers in Ecology and Evolution, 2018)
Current approaches to biodiversity conservation are largely based on geographic areas, ecosystems, ecological communities and species, with less attention ongenetic diversity and the evolutionary continuum from populations to species. Conservation management generally rests on discrete categories, such as identified species, and, for threated taxa, intraspecific units. Species, in particular, provide a common measure of biodiversity yet in both theory and nature, speciation is typically a protracted process progressing from connected populations to unambiguous species with variable rates of phenotypic, ecological and genetic divergence. Thus, most recognised species are not genetically uniform and are sometimes highly structured into historically isolated populations worthy of consideration as intraspecific units that represent unique genetic diversity for conservation. Genome screens offer unprecedented resolution of structure across taxonomic boundaries in species complexes, and have the potential to oversplit species if not interpreted conservatively. This highlights the blurred line between populations and species, and can confound simple dichotomies of ‘species’ versus ‘not species’. At the same time, like plants, there is increasing evidence than even distantly related animal species can hybridize and exchange genes. A review of conservation legislation reveals that legal definitions of ‘species’ are quite flexible and can accommodate a range of infra-specific taxa and divergent populations, as well as taxonomically recognised species. For example, the legislative definition of a species around the world can include: species, subspecies, varieties, and geographically and/or genetically distinct populations. In principle, this flexibility allows for protection of genetic diversity and maintenance of evolutionary processes at a broad range of infra-specific levels. However, evolutionary biologists often fail to adequately justify and then translate their evidence for genetically defined units into categories suited to assessment under local legislation. We recommend that (i). genomic data should be interpreted conservatively when formally naming species, (ii). concomitantly, there should be stronger impetus and a more uniform approach to identifying clearly justified intraspecific units, (iii). guidelines be developed for recognising and labelling intraspecific data that align with best scientific practice, and (iv). that the more nuanced view of species and speciation emerging from genomic analyses is communicated more effectively by scientists to decision makers.